English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-02-07 16:00:07 · 4 answers · asked by crombieqtpy15 3 in Science & Mathematics Mathematics

Sorry,it cut off.the question has 3 parts.part A>f(x+h) part B.f(x+h)-f(x) part C.f(x+h)-f(x)/h

2007-02-07 16:09:41 · update #1

4 answers

What? Could you tell me what country you're from? I've never seen this kind of writing before. I for one am completely stymied.

2007-02-07 16:03:22 · answer #1 · answered by smcdevitt2001 5 · 0 0

part A>f(x+h) part B.f(x+h)-f(x) part C.f(x+h)-f(x)/h

A. f(x+h) = 3(x+h)^2+5(x+h)-8 (replacing x by x+h)
f(x+h) = 3x^2 + 3h^2 + 6xh + 5x + 5h - 8

B. Substitute values for f(x+h) and f(x)
f(x+h) - f(x) = (3x^2 + 3h^2 + 6xh + 5x + 5h - 8) - (3x^2+5x-8)
f(x+h) - f(x) = 3h^2 + 6xh + 5h

C. f(x+h)-f(x)/h = 3h^2 + 6xh + 5h / h = 3h + 6x + 5

2007-02-08 00:05:14 · answer #2 · answered by Rainmaker 2 · 0 0

I'm not for sure of your exact question but try this:

f(x+h) = 3(x+h)^2 + 5(x+h) - 8

Does that look right?

It's been a while

2007-02-08 00:04:54 · answer #3 · answered by burnholywater 2 · 0 0

f(x)=3x^2+5x-8
=>3x^2+8x-3x-8
=>x(3x+8)-(3x+8)
=>(3x+8)(x-1)
x=8/3,1
for f(x+h) replace x by x+h

2007-02-08 00:05:12 · answer #4 · answered by Rhul s 2 · 0 0

fedest.com, questions and answers